Crystal Growth and Kinetic Behaviour of Pseudoalteromonas espejiana Assisted Biosynthesized Gold Nanoparticles. (22nd July 2020) - Gupta, Rashmi; Kumar, Gourav; Das, Sabya Sachi; Alkahtani, Saad; Alkahtane, Abdullah; Aldahmash, Badr; Alarifi, Saud; Almutairi, Bader; Albasher, Gadah; Nayak, Amit Kumar; Hasnain, Md Saquib
Abstract : Pseudoalteromonas espejiana ( P. espejiana ) is a marine bacterium known for its high resistance to alkalinity. The ability of P. espejiana to reduce Au (III) and biosynthesize gold nanoparticles (AuNPs) is found positive and was confirmed using UV-VIS, EDS, SEM, and TEM studies. Previously, many studies have been reported regarding the crystalline nature of AuNPs; therefore, this research aims at studying the crystal growth behaviour of AuNPs through DLS and TEM studies. Spherically shaped and monodispersed, AuNPs ranging between 5 to 160 nm were obtained with an average particle size of 62 nm. Also, to achieve maximum production of AuNPs, the reaction kinetic study was performed using an ICP-OES method and the effect of various parameters including pH, temperature, rpm, and concentration of substrate was analyzed. During the biosynthesis process, an appropriate phase of nucleation, crystal growth, and saturation was observed and this helped to determine the rate constants and order of reaction. The parameters such as pH profile (pH 9), temperature (30°C), agitation speed (150 rpm), and enzyme substrate ratio (2 : 3) were found to be the best fits for maximum production of low size AuNPs. This demonstrates that in initial few hours, a quick conversion of the ionic gold precursor takes place into metallic gold nuclei, trailed by crystal growth via coalescence of small nuclei. Subsequently, it can be concluded that coalescence processes drive the crystal growth process of AuNPs over a time interval and finally leads to saturation and no newer particle formation in the solution.